1998
DOI: 10.1109/16.711358
|View full text |Cite
|
Sign up to set email alerts
|

High-performance germanium-seeded laterally crystallized TFTs for vertical device integration

Abstract: Abstract-Increasing chip complexity and area has resulted in interconnect delay becoming a significant fraction of overall chip delay. Continued scaling of design rules will further aggravate this problem. Vertical integration of devices will enable a substantial reduction in chip size and thus in interconnect delay. We present a novel technique to achieve vertical integration of CMOS devices. Germanium is used as a seeding agent at the source and/or drain of thin film transistors (TFT's) to laterally crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 14 publications
(12 reference statements)
2
42
0
Order By: Relevance
“…Ge-seeded lateral crystallization of ␣-Si was originally proposed by Subramanian et al 12,13 to exploit the long incubation time of nucleated grains to achieve lateral crystallization. It was reported that Ge introduces an additional nucleation site by the formation of a SiGe layer at the Ge-Si interface which crystallizes faster than pure Si at any given temperature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ge-seeded lateral crystallization of ␣-Si was originally proposed by Subramanian et al 12,13 to exploit the long incubation time of nucleated grains to achieve lateral crystallization. It was reported that Ge introduces an additional nucleation site by the formation of a SiGe layer at the Ge-Si interface which crystallizes faster than pure Si at any given temperature.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In a previous article, we reported a new low-temperature ͑500°C͒ ␣-Si crystallization phenomenon that occurs at the perimeter of a Ge layer grown on ␣-Si through a window in a SiO 2 layer.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For the devices on the upper planes, however, different fabrication methods are required. Several techniques, based on laser recrystallization [41] or seed crystallization [42], are used to produce CMOS or SOI devices on the upper planes.…”
Section: Introductionmentioning
confidence: 99%